Practical experience of Moscow universities for the creation and development of science and technology parks - V. A. Dyukarev (Тонкие химические технологии, 2012)
The work deals with the organizational-economic mechanism of the creation and development of scientific and technological parks as habitats for small high-tech firms and innovative enterprises. With the 20 years of experience of development of the Science Park of Lomonosov Moscow State University and the formation of the innovative-technological complex of Moscow State University of Fine Chemical Technologies named after M. V. Lomonosov as examples, the mechanisms for the creation, establishment and development of scientific and technological parks is described. The article analyzes the interaction of science parks with small innovative enterprises being set up in the system of higher education in Russia. A brief analysis of the funding sources for science parks - commercial banks, venture capital funds, and public spending - is given. The work is aimed at professionals in the field of management of scientific and technical progress.